Ethno-racial variations in mental health symptoms among sexually-active gay, bisexual, and other men who have sex with men in Vancouver, Canada: a longitudinal analysis - Seraph L. Bao; Gbolahan Olarewaju; Lu Wang; Jordan Sang; Julia Zhu; Nathan J. Lachowsky; Allan Lal; Aidan Ablona; Darren Ho; Fahmy Baharuddin; Lorenz Villa; Sandy Lambert; et al. (BMC, 2024)
Abstract Background Minority stress from racism and heterosexism may uniquely interact to impact the mental health of racialized sexual minorities. We examined variations in anxiety and depressive symptoms by reported by ethno-racial identity among gay, bisexual, and other men who have sex with men (gbMSM) in Vancouver, Canada. Methods We recruited gbMSM aged ≥ 16 years from February 2012 to February 2015 using respondent-driven sampling (RDS). Participants completed computer assisted self-interviews (CASI) at enrollment and every 6 months until February 2017. We examined factors associated with moderate/severe anxiety and depression scores (> 10) on the Hospital Anxiety and Depression Scale (HADS) and differences in key explanatory variables including sociodemographic, psychosocial, and substance use factors. We used multivariable mixed effects models to assess whether moderate/severe scores were associated with ethno-racial identity across all visits. Results After RDS-adjustment, of 774 participants, 79.9% of participants identified as gay. 68.6% identified as white, 9.2% as Asian, 9.8% as Indigenous, 7.3% as Latin American, and 5.1% as other ethno-racial identities. Participants contributed a median of 6 follow-up visits (Q1-Q3: 4-7). In the multivariable analysis, Asian participants had decreased odds of moderate/severe anxiety scores compared to white participants (aOR = 0.39; 95% CI: 0.18-0.86), and Latin American participants had decreased odds of moderate/severe depression scores compared to both white (aOR = 0.17; 95% CI: 0.08-0.36) and Asian (aOR = 0.07; 95% CI: 0.02-0.20) participants. Conclusion Asian and Latino gbMSM reported decreased mental health symptoms compared to white participants. Asian and Latino gbMSM in Vancouver appear to manage multiple minority stressors without adversely affecting their mental health.